An Automatic Synthesis of Musical Phrases from Multi-Pitch Samples - PLUTA, Marek Janusz; SPAŁEK, Leszek Jędrzej; DELEKTA, Rafał Jacek (Archives of Acoustics, 2017)
Sound synthesizers are a natural element of a musician’s toolset. In music arrangement, samplers can often produce satisfactory results, but it requires a combination of manual and automatic methods that may be arduous at times. Concatenative Sound Synthesis reproduces many of natural performance- and expression-related nuances- but at a cost of high demand for processing power. Here, another method of musical phrase synthesis aimed at music arrangement is presented that addresses these and other related issues. Contrary to common practice, we propose to record and utilize sound samples containing not one, but short sequences of pitches. In effect, natural pitch transitions are preserved and phrases appear to be much smoother, despite using very limited set of performance rules. The proof-of-concept implementation of the proposed method is discussed in detail along with attempts at optimizing the final sound effects, based on auditory tests. The limitations and future applications of the synthesizer are also discussed.